Identification of Pilus-Like Structures and Genes in Microcystis aeruginosa PCC7806 - Nakasugi, Kenlee (American Society for Microbiology, 2005)
Four putative type IV pilus genes from the toxic, naturally transformable Microcystis aeruginosa PCC7806 were identified. Three of these genes were clustered in an arrangement which is identical to that from other cyanobacterial genomes. Type IV pilus-like appendages were also observed by electron microscopy.